2023
DOI: 10.31234/osf.io/q7r58
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncommon Errors: Adaptive Intuitions in High-Quality Media Environments Increase Susceptibility to Misinformation

Reed Orchinik,
Cameron Martel,
David Gertler Rand
et al.

Abstract: Belief in misinformation has been linked in part to digital media environments promoting reliance on intuition -- which in turn has been shown to increase belief in falsehoods. Here we propose that this apparently irrational behavior may actually result from ecologically rational adaptations to complex environments. In a large survey experiment, we test whether intuitive belief in misinformation may result from these rational adaptations by randomizing participants to be shown either a largely true or largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Here we applied drift diffusion modeling (DDM). In doing so, we are among the first to reveal the choice processes underlying news sharing behavior (see Lin et al, 2023;Orchinik et al, 2023). We first consider participants' overall news sharing tendency (across true and false news) before the interventions (at baseline).…”
Section: Decision-making Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we applied drift diffusion modeling (DDM). In doing so, we are among the first to reveal the choice processes underlying news sharing behavior (see Lin et al, 2023;Orchinik et al, 2023). We first consider participants' overall news sharing tendency (across true and false news) before the interventions (at baseline).…”
Section: Decision-making Processesmentioning
confidence: 99%
“…News sharing behavior in our task was simulated and we used half true and half false news trials, which may differ from real-world experiences and veracity base rates (Orchinik et al, 2023).…”
Section: Limitationsmentioning
confidence: 99%
“…Would the effects of blatantly implausible headlines on judgments of plausibility persist even in a more realistic environment, in which plausibility and truth were correlated? To test this, we reanalyzed data from Orchinik et al (13).…”
Section: Study 4: Evaluations When Plausibility and Veracity Are Linkedmentioning
confidence: 99%
“…While recent work has shown that prior exposure to the same false story can make that story more believable (9)(10)(11), it is not clear whether exposure to one set of implausible claims in news could make other, unrelated stories seem more or less plausible by contrast. On the one hand, a high prevalence of implausible news stories could make consumers more generally skeptical, falling for fewer inaccurate headlines while also disbelieving accurate ones (12,13). Such an assimilation effect would converge with similar work on the role of prevalence in perceptual signal detection (14), in which a high prevalence of signals (in this case, implausible news stories) can make them easier to accurately recognize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation